Association of healthy lifestyles on the risk of hypertension, type 2 diabetes mellitus, and their comorbidity among subjects with dyslipidemia - Hu, Peng; Zheng, Murui; Duan, Xueru; Zhou, Huanning; Huang, Jun; Lao, Lixian; Zhao, Yue; Li, Yi; Xue, Meng; Zhao, Wenjing; Deng, Hai; Liu, Xudong (Frontiers in Nutrition, 2022)
Background: Adherence to a healthy lifestyle could reduce the risk of hypertension and diabetes in general populations; however, whether the associations exist in subjects with dyslipidemia remains unclear. This study aimed to investigate the integrated effect of lifestyle factors on the risk of hypertension, type 2 diabetes mellitus (T2DM), and their comorbidity among subjects with dyslipidemia. Methods: 9,339 subjects with dyslipidemia were recruited from the baseline survey of the Guangzhou Heart Study. A questionnaire survey and medical examination were performed. The healthy lifestyle score (HLS) was derived from five factors: smoking, alcohol drinking, diet, body mass index, and leisure-time physical activity. Odds ratios (ORs) with 95% confidence interval (95% CI) were calculated by using the logistic regression model and the multinomial logistic regression after adjusting for confounders. Results: The prevalence of hypertension, T2DM, and their comorbidity was 47.65%, 16.02%, and 10.10%, respectively. Subjects with a higher HLS were associated with a lower risk of hypertension, T2DM, and their comorbidity. In comparison to the subjects with 0-2 HLS, the adjusted ORs for subjects with five HLS was 0.48 (95% CI: 0.40 - 0.57) and 0.67 (95% CI: 0.54 - 0.84) for hypertension and T2DM. Compared with subjects with 0-2 HLS and neither hypertension nor T2DM, those with five HLS had a lower risk of suffering from only one disease (OR: 0.48, 95% CI: 0.40 - 0.57) and their comorbidity (OR: 0.35, 95% CI: 0.26 - 0.47). Conclusions: The results suggest that the more kinds of healthy lifestyle, the lower the risk of hypertension, T2DM, and their comorbidity among subjects with dyslipidemia. Preventive strategies incorporating lifestyle factors may provide a more feasible approach for the prevention of main chronic diseases.